(untitled) (Collection of scientific works «Modern structures of metal and wood», 2021)
The development of technologies for the manufacture and design of steel structures, together with the development of computer technologies, makes it possible to increase productivity in the building industry. The analysis and generalization of such factors made it possible to identify the main trends and directions of the creation and improvement of metal structures, taking into account the automation of their manufacturing processes and the use of BIM technologies. The highlighted tendencies make it possible to show both new directions for the development of scientific research and directions for the development of practical methodologies for determining the regularities of the stress-strain state of structural systems using steel. Among the main trends, the following are highlighted: digitalization of the metal construction industry; automation and robotization of the manufacturing and assembling processes; science intensity of design and production processes; greening production, evaluating design solutions from the standpoint of environmental safety; complex optimization of design solutions. The authors highlight the next important tasks and prospects for the development of the creation of effective metal structures: the creation and use of high-strength steels C960 and more, the improvement of automated and robotic welding processes for ultra-high-strength steels with various metal thicknesses; development and improvement of the theory of calculation of thin-walled and composite structures, determination of the actual resource of metal structures after long-term operation; introduction into the practice of creating new structures of rational and optimal design approaches with the requirements of long-term operation and life cycle, including progressive collapse, reduction in the cost of fire and anti-corrosion covers for steel structures; improvement of building codes and rules for the design of metal structures; implementation of leading foreign standards and experience; training of modern professional engineers and technicians; development of experimental and theoretical studies of full-scale samples of structures on the basis of creating high- precision information models of structural systems.